Peran Teknologi dalam Pendidikan di Era Globalisas - Lestari, Sudarsri (JURNAL EDURELIGIA, 2018)
The aim of the government in organizing education is to educate the life of the nation. Intelligence is needed by everyone to face the times that have entered the era of globalization.Education in the global era can be interpreted as the integration of national education into world education. In the era of globalization, the progress of the nation is largely determined by the use of science and technology. Technology that is developing now has entered the digital era, where all fields have utilized technology to facilitate work, including in the field of education. Educational technology is a system that is used to support learning so that desired results are achieved. The role of technology in education is implemented in the use of learning media,administrative tools, and lerning resources. The positive impact of technology implementation in education is more efficient in terms of time, cost, logistics and other institutional problems, while the negative impact is that technology can change social life